Autoimmunity to insulin receptor and hypoglycaemia in patient with Hodgkin's disease. - Braund, W; Naylor, B; Williamson, D; Buley, I; Clark, A; Chapel, H; Turner, R (1987)
A 76-year-old man with fasting hypoglycaemia had impaired in-vitro binding of insulin to erythrocyte receptors. The immunoglobulin fraction of his plasma inhibited binding of insulin to normal donor erythrocytes in vitro. Autoantibodies may have stimulated the insulin receptor and produced hypoglycaemia. Hodgkin's disease developed and may have induced the autoimmunity. The hypoglycaemia did not respond to plasmapheresis or azathioprine alone, but it remitted after the addition of prednisolone, and the erythrocyte receptor binding of insulin became normal.